The Role of Civil Society Organizations in Creating Conflict Resolution through Multicultural Education - Ahmad Saefudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2019)
Dermolo as one of the villages in Kembang, Jepara, was ever hit by a conflict under a religious background. This friction involved Islamic and Christian groups. The dispute between the two groups increasingly culminated and seemed to have no end without the presence of the Nation. When the Regional Government of Jepara encountered a deadlock in breaking down this social conflict, the presence of a civil society organization was absolutely necessary. Lakpesdam NU Jepara since 2014 up to now has been trying to extinguish the fire of conflict in Dermolo which was initially triggered by disputes over the use of a worship place. Through a qualitative descriptive approach by utilizing the theory of conflict resolution and multicultural education, this paper finally succeeds in mapping the four multicultural education patterns used by Lakpesdam NU. Those are economic empowerment, religious approaches, empowering women, and empowering village cadres. The result of this academic discourse at the same time provides an alternative methodological offer that can be replicated by the stakeholders of the policy makers, for example the Regional Government and the relevant Regional Apparatus Organization. It can be used as a prototype for civil society organizations and peace activists in settling disputes wrapped in religious sentiment. This kind of inclusive pattern is considered quite successful as a conflict resolution strategy. Lakpesdam NU Jepara is the only institution that has the sympathy of the residents and the Dermolo Government, because it has contributed positively in restoring social harmony between Christian and Islam groups